Pacing strategy: Can analytics help us run faster in cross country? - Lane, S. (Techniques Magazine, 2017)
The purpose of this paper is to analyze the pacing strategies of athletes in championship collegiate cross-country races, for which there now exists a great deal of information. Basic statistical analysis suggests a very strong relationship between pacing and finishing time: relatively even pacing predicts faster times. Or, more accurately, athletes with less positive splits run faster and place higher. While at first glance this seems an obvious and not particularly useful statement, it suggests that the vast majority of championship-level collegiate runners employ sub-optimal pacing. This in turn leads to an important question without an obvious answer: Why do highly-trained athletes, guided by experienced and highly-educated coaches - with every incentive to optimize performance - stray so far from good pacing? High-level programs devote significant resources to nutritionists, psychologists, athletic trainers, and massage therapists; yet they appear to pay inadequate attention to a deceptively important aspect of success.